THE Greening of Carbon Trade. - Taylor, David A. (Americas)
Provides information on carbon dioxide trading projects. Health problems associated with climate change; Impact of deforestation on the environment; How the World Bank explored a way to link market forces to emissions reductions; Cost of the bank's carbon-reduction projects.